2018
DOI: 10.1038/s41598-018-25236-8
|View full text |Cite
|
Sign up to set email alerts
|

Wolbachia significantly impacts the vector competence of Aedes aegypti for Mayaro virus

Abstract: Wolbachia, an intracellular endosymbiont present in up to 70% of all insect species, has been suggested as a sustainable strategy for the control of arboviruses such as Dengue, Zika and Chikungunya. As Mayaro virus outbreaks have also been reported in Latin American countries, the objective of this study was to evaluate the vector competence of Brazilian field-collected Ae. aegypti and the impact of Wolbachia (wMel strain) upon this virus. Our in vitro studies with Aag2 cells showed that Mayaro virus can rapid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
76
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(81 citation statements)
references
References 43 publications
4
76
0
1
Order By: Relevance
“…Aedes aegypti can transmit a number of medically important arboviruses, including dengue, Zika, chikungunya, Mayaro and yellow fever viruses [1][2][3][4][5]. Together, these viruses cause significant morbidity and mortality across the world, with an estimated 100 million people experiencing a symptomatic dengue virus (DENV) infection each year [6].…”
Section: Introductionmentioning
confidence: 99%
“…Aedes aegypti can transmit a number of medically important arboviruses, including dengue, Zika, chikungunya, Mayaro and yellow fever viruses [1][2][3][4][5]. Together, these viruses cause significant morbidity and mortality across the world, with an estimated 100 million people experiencing a symptomatic dengue virus (DENV) infection each year [6].…”
Section: Introductionmentioning
confidence: 99%
“…aegypti was nanoinjected into naïve mosquitoes, with 69% of mosquitoes becoming infected. Other laboratory studies also confirm the ability of this vector to transmit MAYV(14,16,34). Therefore, our results confirm that this vector has a great potential for infection and transmission of MAYV and therefore, play an important role in the transmission of this virus, if it gets urbanized.…”
Section: Discussionmentioning
confidence: 62%
“…In general, these mosquitoes presented high levels of infection in heads+thoraces at 14 dpi, averaging 9.6×10 4 and 4.7×10 4 viral particles, for replicates A and B, respectively. A previous study by Pereira et al ., 2018(34), showed that Ae. aegypti mosquitoes from Rio de Janeiro were highly susceptible to MAYV, presenting a higher number of viral copies than those obtained in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations